For Ourselves, Our Neighbours, Our Homelands: Religion in Folklorama’s Israel Pavilion - Bramadat, Paul (Ethnologies, 2001)
Winnipeg’s Folklorama is the largest and longest-running multicultural festival in the world. Local ethnic groups present outsiders (and insiders) with cultural displays, foods, and usually an ethnic performance of some kind. The fact that members of these groups must formally decide how they will represent themselves makes this festival an excellent opportunity to understand the ways groups use these festivals to interact with the broader Canadian society. Although festival managers caution individual pavilion organisers to avoid provocative political or religious issues when designing their pavilions, in the process of depicting particular cultures, ethnic religious traditions are often expressed. In this article, the author focuses specifically on the place and depiction of religions (mainly Islam and Judaism) in the Israel Pavilion. This analysis reveals that the depictions of religion in this pavilion serve to further some of the specific and general goals of the community, including the reduction of local ignorance and anti-Semitism, the preservation of Jewish identity, and the promotion of pro-Israel sentiment.